Oldest record of Machimosaurini (Thalattosuchia, Teleosauroidea): teeth and scavenging traces from the Middle Jurassic (Bajocian) of Switzerland - Torsten M. Scheyer; Michela M. Johnson; Dylan Bastiaans; Feiko Miedema; Erin E. Maxwell; Christian Klug (Royal Society Open Science, 2024)
The Jurassic period was a time of major diversification for Mesozoic marine reptiles, including Ichthyosauria, Plesiosauria and thalattosuchian Crocodylomorpha. The latter originated in the Early Jurassic and thrived during the Late Jurassic. Unfortunately, the Middle Jurassic, a crucial time in their evolution, has a poor fossil record. Here, we document the first evidence of macrophagous/durophagous Machimosaurini-tribe teleosauroid thalattosuchians from the late Bajocian (ca 169 Ma) in the form of three robust tooth crowns with conical blunt shapes and anastomosed pattern of thick enamel ridges towards the apex, associated with the skeleton of a large ichthyosaur lacking preserved tooth crowns. The tooth crowns were found on the posterior section of the lower jaw (left angular), a lacrimal and the axis neural arch of the ichthyosaur. In addition, some of the distal sections of the posterior dorsal ribs of the ichthyosaur skeleton exhibit rounded bite marks and some elongated furrows that fit in size and shape with the Machimosaurini teeth. These marks, together with the absence of healing in the rib bone are interpreted here as the indicators of peri- to post-mortem scavenging by a Machimosaurini teleosauroid after the large ichthyosaur carcass settled on the floor of a shallow ocean.